Workload on Nurses Psychological Well-Being - Dhiya Afsha; Pundani Eki (Universitas Negeri Semarang, 2024)
Based on the results of a pre-research, several nurses in Banyumas Regency experienced a workload that surpassed their abilities, which made the nurses experience mental and physical fatigue. Most impacts nurses feel are emotional instability when working, fatigue easily, back pain, and headaches when working, most of which are caused by a large number of shifts and are not balanced with the existing nursing staff. This study aimed to investigate the effect of workload on the psychological well-being of nurses in the Banyumas regency. Respondents were selected using a quota sampling technique, and data were analyzed through simple regression analysis. The results showed a positive significant effect between workload and psychological well-being, with workload contributing 8% to the variance in psychological well-being, while 92% was influenced by other factors not examined in this study.